Iterative Channel Estimation For Spatial Modulation Systems Over Fast Fading Channels - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2014)
Spatial Modulation (SM) based on the use of antenna indices to transmit information in addition to the conventional signal constellations has been recently proposed to solve practical problems encountered in MIMO systems. In the literature, estimation of CSI for SM systems is simply investigated by RLS for slow fading channels. However, iterative receivers that offer significant performance gains over a non- iterative when the total number of pilot is not sufficient and the channel is fast fading have not been investigated for SM based systems. In this paper, it shown that the RLS based receiver has a performance degradation for fast fading channels and a new iterative channel estimation techniques is proposed with the necessary signal model to enhance receiver performance for fast fading channels. Computer simulation results indicate that proposed iterative receiver has a significant performance advantage over the RLS based receiver for time-varying Rayleigh channels.
Keywords: Spatial Modulation; Channel Estimation; MIMO; Iterative Receiver; Performance; Capacity